Modelling maize yield, soil nitrogen balance and organic carbon changes under long-term fertilization in Northeast China. (1st January 2023) - Yang, Jingmin; Jiang, Rong; Zhang, Hongwei; He, Wentian; Yang, Jingyi; He, Ping
Abstract: Optimized fertilization is an effective strategy for improving nitrogen (N) use efficiency and maintaining high crop yield, but its long-term impacts on soil organic carbon (C) and inorganic N dynamics remain unclear. The objectives of this study were to 1) explore the economic optimum N rate and evaluate the DSSAT CERES-Maize model using the measurements from three 3-year maize ( Zea mays L.) field experiments, in Gongzhuling and Yushu County, Northeast China, and 2) assess the long-term impacts of farmers' N rate (N250), optimum N rate (N180) and organic-inorganic combined N rate (MN180) on maize yields, soil N and C changes from 1985 to 2020. Results showed that similar maize yields of 8000–11, 000 kg ha −1 were achieved under the average economic optimum N rate of 170 kg N ha −1 relative to N250 in both counties. Good agreements were observed between the simulated and measured maize yield, above-ground biomass, N uptake and soil nitrate (NO3 − -N). Long-term simulation confirmed that N180 and MN180 can achieve the same yield as N250 in both counties. The lowest annual soil inorganic N balance, NO3 − -N leaching, and nitrous oxide (N2 O) and ammonia (NH3 ) emissions were achieved under MN180, followed by N180 in both sites. Higher NO3 − -N leaching was found in sandy clay loam soil than silt clay loam and clay loam soils. Average soil organic C (SOC, 0–0.2 m) increased from 1.3 to 2.4% in Gongzhuling and from 2.2 to 2.4% in Yushu under MN180 during the 35-year period, but it showed declining trends under N180 and N250. We concluded that the economic optimum N rate could be an option to replace current farmers' N rate for the continuous maize. Substitution of inorganic fertilizer by 20–30% manure under the optimum N rate showed advantage on maintaining high yield, reducing soil inorganic N losses as well as increasing SOC stock for sustainable agriculture. Highlights: Economic optimum N rate saved 23–76 kg N ha −1 compared with the maximum N rate. DSSAT well simulated maize growth and soil N dynamics under multiple sites. Soil N balance and SOC were simulated under long-term fertilization scenarios. Substitution with 20–30% manure under optimum N rate maintained maize yields with high SOC and low N losses.